Kinetic modeling of microwave‑assisted esterification for biofuel additive production: conversion of levulinic acid with pentanol using Dowex® 50WX8 catalyst (2024)
ABSTRACT: This study explores the esterifcation of levulinic acid with 1-pentanol, employing Dowex® 50WX8 as a catalyst under microwave irradiation. Key parameters such as the pentanol/acid molar ratio, temperature, and catalyst loading were evaluated and utilized for kinetic modeling. The kinetic behavior of the reaction was investigated using a dual-model approach: a pseudo-homogeneous model to account for the microwave efect and catalytic contributions modeled through LHHW and Eley–Rideal mechanisms. The best model was chosen based on statistical results obtained from Markov Chain Monte Carlo (MCMC) analysis, which involved an LHHW model with the surface reaction as the limiting step, resulting in an activa- tion energy of 50.6 kJ mol−1 for the catalytic synthesis of pentyl levulinate. The role of the alcohol in the esterifcation route was explained, and catalytic stability was confrmed, with the catalyst maintaining activity over multiple cycles. The absence of mass transfer limitations was proved using the Weisz–Prater criterion. A plausible reaction pathway was proposed for the levulinic acid esterifcation over the 50WX8 catalyst.